Menschen mit Handicap und Sport - Bansi J; Kesselring J (Dynamic Media Sales Verlag, 2015)
Background: Multiple Sclerosis (MS) is a chronic immune-mediated disease of the central nervous system, accompanied by varying inflammatory manifestations, demyelization and axonal loss. With chronic progressive or relapsing-remitting disease onsets, persons with MS (pwMS) progressively develop impaired functional capacity and show reduced physical activity compared to healthy controls. The role of rehabilitation with exercise as a central component has become an important aspect in the process of reactivating pwMS. The primary aims of rehabilitation are therefore to increase levels of activity and participation leading to increasedindependence of the participants.Methods: Compared to other training modalities, endurance training is well studied and has become an efficient strategy in rehabilitation of pwMS,improving fatigue and health-related quality of life. The most common form is usage of a cycle ergometer but aquatic-exercise and yoga have also been studied. The main goal of resistance training is the general improvement of force components using different resistors. An individual-suited resistance training program impacts maximal force, core-stability, arm, leg and trunk muscles of pwMS.Discussion: Physical activity impacts various growth factors in the central nervous system, primarily via the brain-derived neurotrophic factor (BDNF), the Insulin Growth Factor-1 (IGF-1) and the Vascular Endothel Growth Factor (VEGF). The congnition-promoting effect is achieved via improvement of the metabolic situation in brain tissue, contributing to an increase in brain volume around the Hippocampus. The outstanding cellular adaptation of the BDNF concentrations can be influenced to various degrees by variations in the training protocol.Conclusion: Rehabilitation with exercise is a central component in the process of reactivating pwMS. Evidence shows that exercise training in pwMS has the potential to target and improve many components outlined in the ICF model. The reviewed effects of exercise for pwMS have demonstrated improvements inaerobic and functional capacities, fatigue and muscle weakness.KEY WORDS: Multiple Sclerosis, Exercise, Endurance Training, Resistance Training